THE EFFECTS OF LACTIC ACID BACTERIA GROWTH INHIBITORS OF STAPHYLOCOCCUS EPIDERMIDIS SUPPLEMENTATION ON THE QUALITY OF ANTI-MICROBIAL LOTION - Zulfa, Rozifatul; Ramona, Yan; Arpiwi, Ni Luh (jfpublisher, 2024)
Staphylococcus epidermidis infections of the skin can cause boils, itching and long-lasting sores. Currently, around 75% to 90% of S. epidermidis infection cases are resistant to the antibiotic methicillin. Thus, this becomes a concern in the health sector. This research aims to discover a new method to treat S. epidermidis infection by using lactic acid bacteria as its opponent, so that the use of antibiotics can be reduced. The physical test includes confirmation of Lactic Acid Bacteria (LAB), inhibition test of lab on S. epidermidis, lotion formulation, organoleptic and homogeneity test of lotion, lotion hedonic test, LAB total plate count test in lotion, and data analysis using Microsoft Excel, Statistical Program Service Solution (SPSS), and ANOVA test. Lactic acid bacteria isolates were obtained from previous research stocks and tested for their ability to inhibit S. epidermidis in vitro. These lactic acid bacteria were added to the lotion. The favorability level of consumers to the lotion was also tested. The results indicated that lactic acid bacteria were able to inhibit the growth of S. epidermidis and remained effective until the seventh day. In addition, respondents provided a positive response to the physical quality of the lotion that contained lactic acid bacteria.